Application of Kahoot Game Application Based Assessment in Class Discussion Learning Model Action to Improve Students' Arabic Learning Outcomes - Rosfiani, Okta; Shaputra, Rizki; Muchtar, Ahmad Dedi; Razaq, Fidi (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
The more advanced the times, the more sophisticated the development of technology. No exception to the technology that should be utilized as much as possible by educators in teaching and learning activities in the classroom. possible by educators in teaching and learning activities in the classroom. One of them is of which is that educators can apply the Kahoot application as an assessment tool for learning in the classroom as an effort to create a learning atmosphere so that learning in the classroom as an effort to create a conducive learning atmosphere and conducive and save time in the process of assessing student learning outcomes.This research aims to overcome the problems that occur in the classroom during teaching and learning activities. classroom when teaching and learning activities take place as an action taken to improve students' learning outcomes. to improve the learning outcomes of Arabic language of class X students by applying Kahoot game-based assessment in the action model. Kahoot game-based assessment in the action of Class Discussion learning model. This research uses the Classroom Action Research (PTK) method which was implemented in SMA Muhammadiyah 25 Setiabudi Pamulang, South Tangerang. This research was conducted in two cycles. First, the pre-cycle stage and cycle 1 in its implementation using the Classroom Discussion learning model which learning model consisting of 5 phases (Clarifying the purpose and estabilishing the set, Focusing the Discussion, Controlling the Discussion, Ending the Discussion). Discussion, Controlling Discussion, Ending Discussion, Debriefing)The results of the study found that students' Arabic language learning outcomes The pre-cycle stage to the cycle 1 stage. the completeness of student learning outcomes only reached 47% while the cycle 1 stage the completeness of student learning outcomes has increased. Motivation of students to learn and foster the spirit of challenged students to participate in classroom learning activities